PENGARUH ENVIRONMENTALISME DAN PERILAKU MASYARAKAT TERHADAP TINGKAT KESEHATAN DI WILAYAH KERJA PUSKESMAS PUJUD - Dessyka Febria; Dedi Afandi; Efriyeldi Efriyeldi (Jurnal Ilmu Lingkungan, 2016)
The lack of the enviromentalism, the behavior of clean and the healthy life can lead to health problems such as desease based on the environment is ISPA and diarrhea. This study is aimed to analyze the effect of the environmentalism and the public behavior on the level of health in Puskesmas Pujud area. This study is quantitative analysis in of Cross Sectional. This study was conducted on may 2015, data is taken using a questionnaire. Analysis of data used on this study is statistical analysis of corelation Rank Spearman and F test with level of significant 0,05. The result of the study is showed the environmentalism with r-value = 0.864 which the environmentalism is positively correlated very strongly on the level of health. Than, the public behavior with r-value = 0.873 which the public behavior is positivley correlated very strongly on the level of health. For statistical hypothesis testing is showed F count is hinger than F tables. The environmentalism and the public behavior is affect of the level of health in Puskesmas Pujud area.